Markers of circulating tumour cells in the peripheral blood of patients with melanoma correlate with disease recurrence and progression. (15th November 2012) - Reid, A.L.; Millward, M.; Pearce, R.; Lee, M.; Frank, M.H.; Ireland, A.; Monshizadeh, L.; Rai, T.; Heenan, P.; Medic, S.; Kumarasinghe, P.; Ziman, M.
Summary Background Multimarker quantitative real‐time polymerase chain reaction (qRT‐PCR) represents an effective method for detecting circulating tumour cells in the peripheral blood of patients with melanoma. Objectives To investigate whether the phenotype of circulating melanoma cells represents a useful indicator of disease stage, recurrence and treatment efficacy. Methods Peripheral blood was collected from 230 patients with melanoma and 152 healthy controls over a period of 3 years and 9 months. Clinical data and blood samples were collected from patients with primary melanoma (early stages, 0–II, n = 154) and metastatic melanoma (late stages, III–IV, n = 76). Each specimen was examined by qRT‐PCR analysis for the expression of five markers: MLANA, ABCB5, TGFβ2, PAX3d and MCAM. Results In total, 212 of the patients with melanoma (92%) expressed markers in their peripheral blood. Two markers, MLANA and ABCB5, had the greatest prognostic value, and were identified as statistically significant among patients who experienced disease recurrence within our study period, being expressed in 45% (MLANA) and 49% (ABCB5) of patients with recurrence (P = 0·001 and P = 0·031, respectively). For patients administered nonsurgical treatments, MCAM expression correlated with poor treatment outcome. Conclusions Circulating tumour cells were detectable at all stages of disease and long after surgical treatment, even when patients were considered disease free. Specifically, expression of ABCB5 and MLANA had significant prognostic value in inferring disease recurrence, while MCAM expression was associated with poor patient outcome after treatment, confirming multimarker qRT‐PCR as a potential technique for monitoring disease status.